PERANCANGAN TAMAN BUDAYA KABUPATEN SAMBAS - Muhammad Ikhsan; Syaiful Muazir; Rudiyono Rudiyono (JMARS: Jurnal Mosaik Arsitektur, 2022)
The traditions inherent in the Sambas community make this area thick with customs in people's lives. The development of human civilization is created over time, as is the case with the people in Sambas. Preservation of culture has started in the past and has been preserved until now. Art and Culture that continues to be maintained over time begins to change even more, worse, many are forgotten. This sustainability has an impact on the values of the community, which is reflected in their daily life. Art and Culture is the identity of the community, it is important that efforts are made to maintain it. As an area that upholds the values of traditional arts and culture in the social life of the city of Sambas, it does not yet have a centralized place to accommodate the traditional activities of the Sambas area. There are no supporting facilities to carry out activities and introduce Arts, Culture and Traditions to the community specifically for present and future generations. Concentration of place to continue to preserve this tradition is needed. Therefore, the existence of the Cultural Park aims to accommodate the cultural activities of the Sambas people. The design of the Cultural Park will not only make it a place for the arts but will become a hierarchy of identity for the Cultural and Arts buildings that exist in this city and aims to reintroduce traditions that have begun to be abandoned by the times. Integrating the content contained in Art, Culture and Tradition preserved with Architectural values, in responding to problems, thinking about conformity to the environment. Through the application of Neovernacular Architecture, it is hoped that it can bring back the Art and Cultural Traditions of the Sambas community.